2018
DOI: 10.1021/jacs.8b03009
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity of Rock-Salt Structure LaO Epitaxial Thin Film

Abstract: We report a superconducting transition in a LaO epitaxial thin film with the superconducting transition onset temperature ( T) at around 5 K. This T is higher than those of other lanthanum monochalcogenides and opposite to their chemical trend: T = 0.84, 1.02, and 1.48 K for LaX (X = S, Se, Te), respectively. The carrier control resulted in a dome-shaped T as a function of electron carrier density. In addition, the T was significantly sensitive to epitaxial strain in spite of the highly symmetric crystal struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 23 publications
10
45
0
Order By: Relevance
“…For example, YO is a narrow gap semiconductor, 9 SmO is a heavy fermionic metal, 10 and LaO is a superconductor. 11 In this study, we report the first synthesis of rock-salt type LuO epitaxial thin films with unusual valence of Lu 2+ (Lu 2+ : [Xe]4f 14 5d 1 ). In stark contrast with high- k insulator Lu 2 O 3 , 24 LuO exhibited a narrow band gap and high electrical conduction with a strong spin–orbit interaction originating from its 5d electron carriers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, YO is a narrow gap semiconductor, 9 SmO is a heavy fermionic metal, 10 and LaO is a superconductor. 11 In this study, we report the first synthesis of rock-salt type LuO epitaxial thin films with unusual valence of Lu 2+ (Lu 2+ : [Xe]4f 14 5d 1 ). In stark contrast with high- k insulator Lu 2 O 3 , 24 LuO exhibited a narrow band gap and high electrical conduction with a strong spin–orbit interaction originating from its 5d electron carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the low work function of LaO, the amount of electrons transferred from LaO to FeSe is even larger than that from STO. In consideration of the fact that the rock-salt structure LaO itself was also reported to be a superconductor (T c ∼ 5 K) 59 , our results suggest that FeSe/LaO might be another interesting platform to study interfacial superconductivity in addition to FeSe/STO.…”
Section: Discussion and Summarymentioning
confidence: 82%
“…A Previous experiment demonstrated that the LaO(001) film deposited on the YAlO 3 (110) surface has a tetragonally distorted rock-salt structure with the lattice constants of a = b = 5.198Å and c = 5.295Å [Fig. 1(a)] 59 . These experimental values were adopted for the bulk part of LaO(001) substrate in our calcula- To find out the most stable epitaxial structure, we studied four possible adsorption sites for FeSe monolayer on LaO(001) surface.…”
Section: Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations